Texting While Driving: Computerized Eye Tracking as a Method to Assess Visual Distraction During Driving Simulations - Litwiler, Scott; Hasley, Joseph P.; Maldonado, Edgar; Segall, Mark; Garman, George (American Journal of Management, 2025)
According to the National Traffic Highway Traffic Safety Administration, distracted driving claimed 3,308 lives in 2022. Few studies have used simulated driving experiences to directly assess the impact on gaze while driving with a cell phone distraction present. In this research, gaze was monitored using a commercial eye tracker mounted to a laptop computer while subjects watched a 10-minute video of normal daytime driving. There was a consistent decrease in objects of interest being observed while text messages appeared. A negative but not statistically significant relationship between the amount of media use (based on responses from the questionnaire) and the amount of time that subjects viewed each text was found (p = 0.072). However, as overall risk for poor driving increased, gaze related to other vehicles decreased (p = 0.014). These results reveal that having a cellphone while driving likely impairs one's ability to notice potentially hazardous conditions on the road that could lead to the harm of the driver or others.